THE IMPACT OF MINDFULNESS-BASED PRACTICES ON REDUCING STRESS AND IMPROVING ATTENTION IN PRESCHOOLERS - Karimova Shoira Bakhtiyarovna; Botirova Mukarram Muydinovna (The Bioscan, 2025)
Mindfulness-based practices (MBPs) have emerged as a powerful tool for enhancing mental health and cognitive functioning across diverse populations, including adults, adolescents, and school-aged children. However, their application in early childhood, particularly among preschoolers aged 3 to 6 years, remains an underexplored area of research. This article synthesizes current findings on the impact of mindfulness-based interventions (MBIs) on reducing stress and improving attention in preschoolers, a demographic that is uniquely vulnerable to stress and still developing foundational cognitive and emotional skills. Early childhood is a critical period for brain development, and exposure to chronic stress during this time can lead to long-term adverse outcomes, including impaired attention, emotional dysregulation, and academic difficulties. Mindfulness practices, which emphasize present-moment awareness and non-judgmental acceptance, offer a promising approach to mitigating these challenges. Emerging evidence suggests that developmentally adapted MBPs, such as mindful breathing, body scans, and sensory-based activities, can effectively reduce stress-related behaviors and enhance attentional control in preschoolers. Studies have reported reductions in cortisol levels, a biological marker of stress, as well as improvements in emotional regulation and coping skills. Additionally, mindfulness practices have been shown to strengthen attentional capacities, including sustained focus, impulse control, and cognitive flexibility, which are essential for learning and social interactions. Despite these promising findings, the field faces several challenges, including the need for age-appropriate interventions, engagement strategies tailored to young children, and reliable measurement tools for assessing outcomes in this population. This article highlights the potential of MBPs to support healthy development in preschoolers by fostering resilience, self-awareness, and attentional skills. It also calls for further research to establish standardized protocols, evaluate long-term effects, and address implementation barriers. By integrating mindfulness-based practices into early childhood education, educators and caregivers may be able to equip young children with the tools they need to navigate stress, enhance their attention, and thrive in their formative years.